LA ROCA DEL ABSOLUTO, LA MUERTE Y EL PODER SOBRE EL LAGO (Revista Temporis[ação] (ISSN 2317-5516), 2017)
The Great Coatlicue has played an important role in Octavio Paz’s art critical activity, both in his perception as a viewer, as well as in his transformation of such an experience into writing. In Octavio Paz’s thinking in general and within his aesthetics in particular, there seems to be a stratum of relationship with the Mesoamerican past that finds expression through the Great Coatlicue. This sculpture has provided Paz with the material attributes, iconographic signs and symbols, compositional devices, as well as the epistemological foundations to approach the work of such different artists as Rivera, Tamayo, and especially Duchamp. In Duchamp’s Bride, Paz has been able to bring together so far apart examples as a Bengali representation of Kali, the courtly love code of Provence, and the myth of Diana and Acteon. By blending the particular aspects of the Mesoamerican representation with its Old World counterparts, Paz attempts to maintain the universal considerations of the phenomena of creation and destruction through the core relationship between woman and reality. In “The Petrifying Petrified” we find the final confluence, and identity between the Woman as a cosmic force, the Great Coatlicue as Imago Mundi in its Aztec version, and Mexico-Tenochtitlan, the City on the Island on the Lake, as the sacred place which symbolizes the Center of the World. Here we witness the incarnation of the woman and her landscape. And vice versa: the landscape becomes flesh. Time and space have become one: their transitory stage is a sculpture, which is a woman, a city, a landscape. This triadic image is reflected by the poem resolving into its unity and singularity the multiple richness of the world. For Octavio Paz the Great Coatlicue “shows the entrails of being.” This statue is the manifestation of absence; in her image void is incarnated. In an analogous way, Paz’s vision is embodied in a poem. There, Paz achieves what he himself demands from a real modern art, “that which, far from masking emptiness, will manifest it.”